Effects of mantle rheologies on viscous heating induced by glacial isostatic adjustment - Huang, Ping Ping (author); Wu, Patrick (author); van der Wal, W. (author) (Geophysical Journal International, 2018)
It has been argued that viscous dissipation from mantle flow in response to surface loading during glacial cycles can result in short-term heating and thus trigger transient volcanism or changes in mantle properties, which may in turn affect mantle dynamics. Furthermore, heating near the Earth's surface can also affect the stability of ice sheets. We have studied the magnitude and spatial-temporal distribution of viscous heating induced in the mantle by the realistic ice model ICE-6G and gravitationally consistent ocean loads. Three types of mantle rheologies, including linear, non-linear and composite rheologies are considered to see if non-linear creep can induce larger viscous heating than linear rheology. We used the Coupled-Laplace-Finite-Element model of Glacial Isostatic Adjustment (GIA) to compute the strain, stress and shear heating during a glacial cycle. We also investigated the upper bound of temperature change and surface heat flux change due to viscous heating. We found that maximum viscous heating occurs near the end of deglaciation near the edge of the ice sheet with amplitude as high as 120 times larger than that of the chondritic radioactive heating. The maximum heat flux due to viscous heating can reach 30 mW m -2 , but the area with large heat flux is small and the timescale of heating is short. As a result, the upper bound of temperature change due to viscous heating is small. Even if 30 glacial cycles are included, the largest temperature change can be of the order of 0.3 °C. Thus, viscous heating induced by GIA cannot induce volcanism and cannot significantly affect mantle material properties, mantle dynamics nor ice-sheet stability. The Author(s) 2017. Published by Oxford University Press. All rights reserved. Astrodynamics & Space Missions